ANALISIS SENYAWA ANTIRADIKAL BEBAS PADA MINYAK DAGING BIJI KEPUH (Stercuria foetida L) - Gede Bawa, I G. A. (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010)
Analysis of anti freeradical compounds from Kepuh (Sterculia foetida L.) seed flesh oil has been conducted. The isolation of kepuh seed flesh was carried out by maseration using n-hexane and ethanol. Anti freeradical test was carried out by spectroscopy method using DPPH as free radical. The analysis of the compounds extracted accomplised was used Gas Column Mass Spectrometry (GC-MS). 900 gram Kepuh seed yielded 250 mL oil n-hexane extract and 59,5 mL from ethanol extract. The result of the anti freeradical test showed that the oil from n-hexane extract was not potencial as a anti freeradical agent while the oil from ethanol extract has a potency as a anti freeradical agent with damping percentage of 55,07% during 5 minutes and 85,05% during 60 minutes. The analysis using GC-MS, showed that ethanol extract oil from the flesh of kepuh seed contained 8 major component with relative concentration of methyl palmitate 3956,783 ppm (235,428 mg); palmitic acid 1837,414 ppm (109,326 mg); ethyl palmitate 39288,783 ppm (2337,683 mg); (14Z,16Z)-ethyl octadeca-14,16-dienoate 17062,660 ppm (1015,228 mg); (15Z,17Z)-methyl nonadeca-15,17-dienoate 19988,563 ppm (1189,319 mg); ethyl stearate 4365,666 ppm (259,757 mg); (1Z,4Z)-1-methoxy-9,9,10,14-tetramethyl pentadeca-1,4-diena 22421,631 ppm (1334,087 mg); and (1Z,12Z,16Z)-1-ethoxy-6 methoxy octadeca 1,12,16-triena 78001,041 ppm (4672,262 mg).
Keywords: Sterculia foetida L, anti freeradical, GC-MS